Conformational Changes Required for Reovirus Cell Entry are Sensitive to pH - Thete, Deepti (Virology, 2015)
During cell entry, reovirus particles disassemble to generate ISVPs. ISVPs undergo conformational changes to form ISVP* and this conversion is required for membrane penetration. In tissues where ISVP formation occurs within endosomes, ISVP-to-ISVP* conversion occurs at low pH. In contrast, in tissues where ISVP formation occurs extracellularly, ISVP-to-ISVP* transition occurs at neutral pH. Whether these two distinct pH environments influence the efficiency of cell entry is not known. In this study, we used Ouabain to lower the endosomal pH and determined its effect on reovirus infection. We found that Ouabain treatment blocks reovirus infection. In cells treated with Ouabain, virus attachment, internalization, and ISVP formation were unaffected but the efficiency of ISVP*s formation was diminished. Low pH also diminished the efficiency of ISVP-to-ISVP* conversion in vitro. Thus, the pH of the compartment where ISVP-to-ISVP* conversion takes place may dictate the efficiency of reovirus infection.